2013
DOI: 10.1128/mbio.00250-13
|View full text |Cite
|
Sign up to set email alerts
|

Clade-Specific Virulence Patterns of Mycobacterium tuberculosis Complex Strains in Human Primary Macrophages and Aerogenically Infected Mice

Abstract: In infection experiments with genetically distinct Mycobacterium tuberculosis complex (MTBC) strains, we identified clade-specific virulence patterns in human primary macrophages and in mice infected by the aerosol route, both reflecting relevant model systems. Exclusively human-adapted M. tuberculosis lineages, also termed clade I, comprising “modern” lineages, such as Beijing and Euro-American Haarlem strains, showed a significantly enhanced capability to grow compared to that of clade II strains, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 33 publications
10
135
0
1
Order By: Relevance
“…Besides, Manu lineage strains were recently reported to be associated with HIV infection (45), and Manu and EAI lineages were shown to be closely related. In a mouse model study, mice infected with EAI strains showed better survival than those infected with Beijing strains (33), which was similar to the phenomenon that patients with mixed infections had less extensive pulmonary pathology and increased immunological tolerance compared with those with single infections (14). Thus, the unique properties of the Manu2 lineage need further investigations in order to clarify its relevance to mixed infections.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Besides, Manu lineage strains were recently reported to be associated with HIV infection (45), and Manu and EAI lineages were shown to be closely related. In a mouse model study, mice infected with EAI strains showed better survival than those infected with Beijing strains (33), which was similar to the phenomenon that patients with mixed infections had less extensive pulmonary pathology and increased immunological tolerance compared with those with single infections (14). Thus, the unique properties of the Manu2 lineage need further investigations in order to clarify its relevance to mixed infections.…”
Section: Discussionmentioning
confidence: 65%
“…The similar situation also appeared in Vietnam, where the most isolates of mixed infections were found to belong to the East African-Indian (EAI) lineage (14). Compared with Beijing strains, EAI strains showed not only less virulence but also a 100-fold lower replication level in lung infections (33). It is noteworthy that the Manu and EAI lineages are believed to be closely related or even derived from a latest common ancestor (34).…”
Section: Discussionmentioning
confidence: 76%
“…tuberculosis (strain H37Rv, ATCC 27294; American Type Culture Collection, Manassas, VA), GFP-expressing M. tuberculosis H37Rv, and M. avium (strain SE01) were grown as previously described (25,26). GFPexpressing M. tuberculosis was generated using the plasmid 32362: pMN437 (Addgene, Cambridge, MA), kindly provided by Prof. M. Niederweis (University of Birmingham, Birmingham, AL) (27).…”
Section: Stimuli and Inhibitorsmentioning
confidence: 99%
“…In line with our previous comparison of in vitro cytokine responses to different M. tuberculosis lineage strains (17), TNF-a and IL-6 induction in this study was higher in lineage 4 (ancient) than in lineage 1 (modern) strains. These lineage effects may depend on strain selection, as shown in a study by Reiling and colleagues (34), who found opposite results. The aim of our study was not to discern lineage effects; therefore, we corrected for these lineage effects in our statistical model.…”
Section: Discussionmentioning
confidence: 71%